A robotic‐assisted hybrid coronary revascularization program: Establishment and early experience in the Middle East. Issue 12 (9th November 2022) - Aluthman, Uthman; Bafageeh, Salman W.; Ashour, Mohammed A.; Barnawi, Hani I.; Bogis, Abdulbadee A.; Alamri, Rawan; Elmahrouk, Ahmed F.; AlGhamdi, Saeed A.; Ismaeil, Nabeel; Shihata, Mohammad; Jamjoom, Ahmed A.
Abstract: Background: Hybrid coronary revascularization (HCR) is a technique that merges coronary artery bypass grafting surgery and percutaneous coronary intervention (PCI) approaches for the treatment of multivessel coronary artery disease. The surgical component of the procedure is minimally invasive and can be done using robotic technology that avoids the need for sternotomy. Our objective is to study all patients who underwent robotic‐assisted HCR (RHCR) to evaluate the feasibility and safety of the procedure during the establishment phase. Methods: This study is a retrospective chart review conducted at King Faisal Specialist Hospital and Research Centre in Jeddah (KFSRC‐J). The study focuses on patients who underwent RHCR between July 2018 to December 2020. The study was approved by the institutional review board #2020‐103. Results: Robotic‐assisted HCR was performed on 78 patients (mean age, 56 years (range, 43–72 years); 89.75% males) during the study phase. Left internal mammary artery grafting was used in all patients. There was no hospital mortality, and the mean hospital and intensive care unit (ICU) stay were 5.8 and 1.4 days, respectively. We found that 93.6% of the patients had no blood transfusion. There were no major adverse cardiac events (MACE) and perioperative MI recorded. There was a 3.8% rate of postoperative complications. The percentage of surgeries converted to conventional and re‐exploration for bleeding were 1.2% and 2.6%, respectively. The average operation time was 164 min. Conclusion: This study emphasizes on the safety and effectiveness of RHCR in treating patients with multivessel coronary artery disease. Moreover, robotic‐assisted hybrid coronary revascularization offers an alternative, functionally complete revascularization option to a selected group of patients with minimal surgical trauma, short hospital and ICU length of stay, quick recovery, and little to no blood transfusion requirement.